IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA (ADD) TAHUN 2020 DI KAMPUNG ADOKI DISTRIK YENDIDORI KABUPATEN BIAK NUMFOR PROVINSI PAPUA - Lesias Hans Yacobus Ronsumbre; Nur Aedah (Universitas Cenderawasih, 2021)
This study aims to describe and analyze in depth the implementation of the Village Fund Allocation policy in Adoki Village, Yendidori District, Biak Numfor Regency, Papua. And look at the factors that support and inhibit it. The research method used is descriptive qualitative. Data collection techniques in the form of interviews and observations. Data analysis includes data reduction, data exposure, and drawing conclusions. The results showed 3 priority programs, namely the field of village administration, development implementation, community development, and for urgent needs. However, during the Covid-19 pandemic, the use of the budget was diverted to the BLT (Direct Cash Assistance) program to support the resilience of the village community to face the pandemic. In the implementation of the Village Fund Allocation policy, in the communication aspect, the distribution pattern is carried out in a structured manner with coordination between institutions at the village level and billboards are also installed as a medium for implementing activities and transparency of budget use at the village hall. In the aspect of resources, all relevant stakeholders at the village level, namely village officials, assistants and the community in the management and implementation of the program, have been limited to supporting facilities. In the Disposition Aspect, the leader proactively socializes with his staff to do a good job in order to maintain public trust. Apsek Bureaucratic Structure used Standard Operating Procedures from the Ministry of Villages for budget management and use and used as a reference in the division of tasks. Supporting factors include the involvement of all relevant stakeholders in the institutional aspect, then village leaders are more proactive in socializing the Village Fund Allocation Program. And the inhibiting factors are the lack of facilities in the management aspect, and the limited facilities and infrastructure that support the implementation of activities.